The Tales - Bozek, Jessica (punctum books, 2023)
Stitching together a post-apocalyptic history from the scraps of fairy tales, war memorials, hunting songs, and disparate scholarship, Jessica Bozek's The Tales traces the violence that humans inflict upon one another. As the central narrative of the Lone Survivor becomes revealed through the mouths of various perspectives, Bozek investigates the language that victims and perpetrators alike use to make sense of (and attempt to forget) the aftermath of violence. From ordinary objects-family photographs, sweaters that unravel, old batteries, and lightbulbs-to the remnants of destroyed art and architecture, an annihilated nation is brought into reality, and the Lone Survivor's story is simultaneously documented and invalidated, becoming "a memorial that will disintegrate over time, gray and fray as most of the dead did not have a chance to."